IEUBK Model to Calculate the Lead Concentration in Blood Children of the Environment which Effect by Lead Emission: Empirical Comparisons with Epidemiologic Data: Developing a Human Health Risk Model to Quantify the Risk Posed by Soil Pb (Al-Nahrain Journal of Science, 2018)
For decades, human health was threaten (especially that of children) by what considered as a potential sources of lead exposure which are: lead-contaminated water, soil, and air. The proposed of the research involve developing an integrated exposure, uptake, and biokinetic (IEUBK) model as a human health risk model to predict the blood lead levels BLL in children. The data set of this project for human health risk posed by Pb contamination in air, water and soil were obtained from previous study achieved in 2014 which carried out on 108 school children (School children in rural areas (n=76 child) and School children in urban areas (n=32child) matched for age. The environmental samples demonstrated that the concentration of lead for air and soil exceeded the international acceptable threshold values. However, the concentration of lead in water was below the threshold value. The BLL value from currently result of IEUBK model was above the agency’s threshold of concern, 10 μg/dL which was documented as children’s BLL lowest level of concern. This predicted values result of BLL was in agreement with actual value of BLL in blood samples of school children for the chosen study. Also, the results of this research confirmed that the high BLL could be attributed to the high lead level in both air and soil of contaminate environment.